2013
DOI: 10.1002/jgrc.20088
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of surface chlorophyll a, autumn‐winter and spring blooms in the southwest Pacific Ocean

Abstract: [1] Ocean color data from the 13 year Sea-viewing Wide Field-of-view Sensor mission are used to examine the distribution of surface chlorophyll a in the southwest Pacific Ocean. The mean surface chlorophyll field is similar to that found by previous workers, with elevated levels in the Subtropical Front and around the subantarctic islands that have an associated shelf. The annual cycle in surface chlorophyll shows a ubiquitous summer bloom in subantarctic water, with autumn, winter, and spring blooms variously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 50 publications
(104 reference statements)
7
94
0
Order By: Relevance
“…The range of chl a concentrations measured in autumn on the C. Plateau (Table ) was in good agreement with previous in situ measurements made on the plateau (0.25–2.00 mg m −3 ) (Heath & Bradford‐Grieve, ) and in SAW east of New Zealand (0.2–0.4 mg m −3 ) (Boyd et al, 1999, Boyd et al, ; Bradford‐Grieve et al, ; Gall et al, ). The high variability (0.1 to >1.5 mg m −3 ) observed on the plateau was consistent with the patchy distributions of chl a observed by satellite data, with elevated levels associated with the Auckland and Campbell islands and the Pukaki Rise in this (Figures and S6) and previous studies (Chiswell et al, ; Heath & Bradford‐Grieve, ; Pinkerton, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The range of chl a concentrations measured in autumn on the C. Plateau (Table ) was in good agreement with previous in situ measurements made on the plateau (0.25–2.00 mg m −3 ) (Heath & Bradford‐Grieve, ) and in SAW east of New Zealand (0.2–0.4 mg m −3 ) (Boyd et al, 1999, Boyd et al, ; Bradford‐Grieve et al, ; Gall et al, ). The high variability (0.1 to >1.5 mg m −3 ) observed on the plateau was consistent with the patchy distributions of chl a observed by satellite data, with elevated levels associated with the Auckland and Campbell islands and the Pukaki Rise in this (Figures and S6) and previous studies (Chiswell et al, ; Heath & Bradford‐Grieve, ; Pinkerton, ).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we argue that the erosion of the thermocline and changes in the MLD represents the perturbations that disrupt the equilibrium within the HNLC microbial system. In line with this interpretation we found a positive, although not significant, relationship between phytoplankton growth rate and the depth of the mixed layer across all regions (R‐Spearman = 0.41, n = 10) (Figures a and S5) that reflects to some extent the phytoplankton response to the vertical entrainment of subsurface nutrients caused by the thermal and wind‐driven erosion of the summer pycnocline (Chiswell et al, ) (Figure S1d). This positive trend suggests that phytoplankton physiology was able to cope with decreasing light exposure associated with the deepening mixed layers without severely compromising their growth.…”
Section: Discussionsupporting
confidence: 76%
“…The first event deepened the mixed layer down to the DCM, and the second brought it below the nutricline. This sequence of events, which began with the mixing of the DCM, followed by an increase of primary production caused by the nutrient supply from deeper layers, induced by increased wind stress, has been previously described by Chiswell et al (). Lavigne et al () indicated that DCM erosion could explain 60% of chlorophyll profiles observed in the Ionian region in December and January.…”
Section: Discussionmentioning
confidence: 99%
“…The relative stability of bloom dynamics suggested by climatological patterns is in contrast to the variability observed spatially and temporally within ecosystems. Regional analyses often reveal complex patterns of meso- scale heterogeneity in bloom dynamics often related to features of the underlying physical environment (Zhao et al, 2013), the physiochemical regime of the ecosystem (Shiozaki et al, 2014), or inter-annual variability of the wind regime (Chiswell et al, 2013;Navarro et al, 2012). However, broad-scale climate dynamics such as the North Atlantic Oscillation (Zhai et al, 2013) and El Nino/ Southern Oscillation (D'Ortenzio et al, 2012) can influence coherent patterns of bloom dynamics.…”
Section: Introductionmentioning
confidence: 99%